2005
DOI: 10.1590/s0034-71672005000100011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da doença hipertensiva específica da gestação em hospital público de São Paulo

Abstract: RESUMOPesquisa descritiva-exploratória, realizada de janeiro a julho de 2002, com INTRODUÇÃOA Doença Hipertensiva Específica da Gestação (DHEG), é uma das complicações mais comuns e de maior morbimortalidade materna e perinatal ocupando o primeiro lugar dentre as afecções próprias do ciclo grávido-puerperal (1)(2)(3)(4)(5)(6) .A DHEG, também denominada pré-eclâmpsia, é caracterizada pela tríade: edema, proteinúria e hipertensão arterial. É uma síndrome que acontece no final do 2º trimestre da gestação e per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 5 publications
0
7
0
17
Order By: Relevance
“…It is known that the support of the family is essential for the good evolution of gestation, as well as the problems that result from it. 21 In this study, the marital situation was one of the risk factors for SGHS, where adolescents and young adults without partner, presented a 50% greater chance of developing SGHS (OR = 1.5). A study conducted by Oliveira and Graciliano 19 when evaluating the factors associated with the SGHS outcome in women between the ages of 13 and 43 at the Maceió Public Maternity in 2013 showed divergent results, in which the single women had a lower risk of developing any of the categories of SGHS (OR = 0.66, CI95%= 0.37-1.15), acting as a protection factor.…”
Section: Modelsmentioning
confidence: 66%
See 1 more Smart Citation
“…It is known that the support of the family is essential for the good evolution of gestation, as well as the problems that result from it. 21 In this study, the marital situation was one of the risk factors for SGHS, where adolescents and young adults without partner, presented a 50% greater chance of developing SGHS (OR = 1.5). A study conducted by Oliveira and Graciliano 19 when evaluating the factors associated with the SGHS outcome in women between the ages of 13 and 43 at the Maceió Public Maternity in 2013 showed divergent results, in which the single women had a lower risk of developing any of the categories of SGHS (OR = 0.66, CI95%= 0.37-1.15), acting as a protection factor.…”
Section: Modelsmentioning
confidence: 66%
“…At this level (Model II), there was a significant association between clinical history of risk and SGHS (p<0.001). It should be noted that, at the intermediate level, single women (p=0.022) and low education (p=0.001) maintained 21,22,23,24 These studies identified possible associations between early maternal mortality and SGHS, pointing out the essential importance of prenatal care in relation to the impact of the disease on the health of adolescent women.…”
Section: Resultsmentioning
confidence: 86%
“…Destas, 40,9% eram primigestas e 45,45% eram adolescentes (31) . A ocorrência de diabete durante a gestação associou-se positivamente com o BPN na análise bivariada.…”
Section: Resultsunclassified
“…Sobrepondo-se à hipertensão, encontram-se a pré-eclâmpsia e a eclâmpsia, responsáveis por taxas elevadas de morbimortalidade materna e perinatal 2-4 e consideradas as principais causas de mortes obstétricas diretas. Com isso, as síndro-mes hipertensivas na gestação tornaram-se um grave problema de saúde pública 5 .…”
Section: Introductionunclassified